MAXSUS TA’LIM MUTAXASSISLARINING STRESSGA CHIDAMLILIK XUSUSIYATLARI ILMIY TADQIQ ETILISHI - Jumaniyozova, N.R. (SCIENCE and SOCIETY, 2024)
This article analyzes the causes and consequences of stressful situations that occur in professionals working with students with disabilities. The theoretical materials of the ongoing scientific research work on increasing stress tolerance are presented. Recommendations have been given about increasing stress resistance, identify coping strategies in problematic situations, and overcome stress in specialists.